Therapeutic interventions and the length of hospital stay for pediatric patients with COVID-19: a multicenter cohort study - Tadashi Ishihara; Takashi Tagami; Atsushi Hirayama; Yuki Nakamura; Koichiro Sueyoshi; Ken Okamoto; Hiroshi Tanaka (Scientific Reports, 2023)
Abstract The evidence for pediatric patients with COVID-19 was very limited, which was attributed to the small number of the cases as well as the rare incidence of severe pneumonia in this population. This retrospective cohort study aimed to identify the characteristics of pediatric patients with COVID-19 in the early period of the pandemic by analyzing Diagnosis Procedure Combination (DPC) data in Japan. This retrospective cohort analysis of Japanese multicenter research on COVID-19 using DPC data compared the outcomes and costs of treatment for pediatric patients with COVID-19. Of 4700 patients with COVID-19, 186 pediatric patients were included in this study. Among the included pediatric patients, 17 received therapeutic drugs specifically for COVID-19, while the remaining 169 pediatric patients received only symptomatic therapy. There were no significant differences in the length of hospital stay (9 vs. 8 days, p = 0.96), and medical cost (97,585 vs. 73,291 JPY) for the intervention and control groups, respectively by multiple regression analysis. This is the first epidemiological study to use DPC data to summarize the pathophysiology of pediatric patients in the early period of COVID-19 pandemic. There was no significant difference in length of hospital stay or medical cost by intervention.